The Influence of Transformational Leadership Style and Performance Benefits on Employee Performance - Herawati, Desi; Qomariah, Nurul; Putu Martini, Ni Nyoman (International Journal of Management Science and Information Technology, 2024)
Human resources (employees or employees) in a company/institution organization are always considered a vital asset for the organization. Performance or work achievement (performance) can be interpreted as achieving work results in accordance with the rules and standards that apply to each organization. Performance can also be said to be the result or output of a process. The aim of this research is to directly determine the transformational leadership style and performance allowances on employee performance with motivation as a mediating variable at the Jember Regency Education Office. The number of samples in this study was 135 respondents, namely employees with ASN status. Description analysis is needed to find out the respondent's description. Measuring instruments in the form of questionnaires need to be tested using validity and reliability tests. To find out the results of the research hypothesis, hypothesis testing is needed. The results of data analysis show that the transformational leadership variable has a positive influence on employee performance. Performance allowances can have a positive influence on employee performance in a government organization, especially the Education Service.